Penerimaan Teknologi ChatGPT Di Kalangan Mahasiswa: Studi Deskriptif Model TAM Pada Mahasiswa Program Studi Teknik Informatika Universitas Negeri Padang - Rahayu Sukma Izzati Dasian; Desriyeni Desriyeni (Pusat Riset dan Inovasi Nasional, 2024)
This research examines the acceptance of ChatGPT technology among students of the 2020 Informatics Engineering study program, Faculty of Engineering, Padang State University using the TAM model. This research aims to describe the acceptance of ChatGPT among students. The type of research used is quantitative research with a case study approach. The method used is descriptive research method. Data collection techniques through observation, interviews and questionnaires. Sampling in this research was by using saturated samples. Research data was obtained from the results of a questionnaire distributed to 89 samples who were informatics engineering students class of 2020. Based on the research results, it can be concluded that there is acceptance of ChatGPT technology among students of the Informatics Engineering Study Program Class of 2020, Faculty of Engineering, Padang State University, with five indicators which are obtained an average value of 2.61. The indicators include (1) Perception of ease of use, obtaining an average value of 2.64 whose interval scale is positive or categorized as good, meaning that the ease of use of ChatGPT so that it does not require special skills can be accepted by students of the Informatics Engineering Study Program Class of 2020. ( 2) Perception of user usefulness, obtained an average value of 2.65 whose interval scale is positive or categorized as good, meaning that ChatGPT provides benefits in helping user performance so that the indicator can be accepted by students of the 2020 Informatics Engineering Study Program. (3) Intention to use , obtained an average score of 2.57, which is a positive interval scale or categorized as good, meaning that the use of ChatGPT which will be reused over a longer period of time can be accepted by students of the 2020 Informatics Engineering Study Program. (4) Real conditions for using the system obtained an average score of 2.60 on a positive interval scale or categorized as good, meaning that users use ChatGPT truly to help user performance so that it can be accepted by students of the Informatics Engineering Study Program Class of 2020. (5) Attitude towards use, gain The average value is 2.61, the interval scale is positive or can be categorized as good, meaning that based on the evaluation of ChatGPT users, the impact of using ChatGPT can be felt so that this indicator can be accepted by students of the 2020 Informatics Engineering Study Program. Even though it is categorized as good, the use of ChatGPT can has a negative impact on students, such as dependence on ChatGPT which will affect students' critical thinking abilities in doing assignments and a lack of social interaction such as discussions because they rely too much on ChatGPT when doing assignments.